ANALISIS PEMANFAATAN AKUN X RIDWAN KAMIL DALAM MEMBANGUN PERSONAL BRANDING DAN KEDEKATAN KULTURAL TERHADAP MASYARAKAT: - Muhamad Iqbal Muttaqin; Ariza Ardiansyah; Achmad Nurmandi (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
This research study discusses social media X which is used by Ridwan Kamil, Governor of West Java Province as a means of building personal branding and cultural closeness to society. The aim of this research is to analyze and measure trends in the X @ridwankamil account in an effort to build personal branding and cultural closeness to society. The method used in this research is a qualitative method and a descriptive approach with data collection techniques using NCapture which is sourced directly from the X platform. Meanwhile, for data analysis techniques, researchers used Nvivo 12, which is presented in the form of descriptive analysis. The results obtained from this research show that his activeness and flexibility in using social media has helped build a good positioning in the eyes of the community as an adaptive leader. Through the use of social media, Ridwan Kamil can interact directly with the audience, reply to their feedback and provide encouragement. His involvement and adaptability on social media has had an impact on increasing his personal branding or positive reputation as well as expanding his relationships and closeness with society at large.